Sexual Socialization: A Seamless Approach in De-emphasizing Rape Scourge in Nigeria - Babatope Matthew Ajiboye (CV. Literasi Indonesia, 2021)
Rape, a mammoth epidemic notoriously having its tentacles covering everywhere like a speed of light that travels through cable implanted in a conduit pipe enclosed in an edifice. This scourge has unmasked its ugly face; of no value nakedness and spiteful fang on the nation in no undersized gauge, thereby consuming and reducing her women-folk to nothing but ciphers of humanity even in their own home; their dignity alienated, emotionally and psychologically dehumanized, made to struggle with societal stigmatization and above all, condemned to a lifetime melancholy trauma. It is on this foundation the paper explores how sexual socialization as a strategy could be utilized in stemming the further increase of the scourge and to ensuring a haven for everyone irrespective of gender. A secondary source was adopted for data collection; it also made use of qualitative analysis which invariably led to inferences drawn and coherent conclusion achieved. Findings revealed that the level of enlightenment and strategy towards rape curtailment in Nigerian society has been so low. The paper recommends that parents must be on their guard by ensuring that children receive sound sexual socialization from home fronts. The paper concluded that rape has been a colossal cankerworm rattling the nation.